Improving Passing Ability Using the Drill Method In Football Games - Asis, Ahmad Syafaat; Ahmad, Ahmad; Marhani, Marhani (Department of Physical Education, Sport, Health and Recreation, 2023)
The aim of this studyto improve passing ability by usingdrill method on studentsSMPN 2 BUA class VIII. This research includes classroom action research.The research subjects were grade VIII students of SMPN 2 BUA, with a total of 32 students, consisting of 18 boys and 14 girls in the 2023/2024 academic year.The meetings in this study were designed in two cycles, namely cycle I and cycle II. Passing data collection was carried out using passing assessment process sheets in cycles I and II. The collected data were analyzed quantitatively. The results of the quantitative analysis of passing data show that the number of students who passed in cycle I was 22 students with a percentage of 69% and the number of students who completed in cycle II was 30 people with a percentage of 94%. The results of the analysis show that there is a significant increase in passing ability. Based on the results of data analysis it was concluded that there was an increase in passing abilityby usingdrill method on studentsSMPN 2 BUA class VIII.